Kajian Etnobotani Tumbuhan Obat Etnis Batak Toba di Desa Sipituhuta Kecamatan Pollung, Kabupaten Humbang Hasudutan, Sumatera Utara - Jamilah Nasution; Riyanto Riyanto; Maisarah L. Gaol (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
The high potential of medicinal plants in Sipituhuta Village can make it easier for people to use these plants for daily needs especially for traditional medicine. This study aims to determine the type of plants that have medicinal properties according to the Toba Batak ethnic in Sipituhuta Village. Methodology used for this study was observation and sample collectioned. Sample was collected based on the interview to local community. The data collected were analyzed descriptively. The results revealed that 40 species from 21 families of plants that contain medicinal properties. The most widely use parts were leaves (20 species or 49%), rhizomes (5 species or 12%); tubers, fruits, stems (3 species or 7% respectively); sap and seeds (1 species or 2%). Key words: medicinal plants; traditional medicine; Toba Batak.